ANALYSIS OF THE DETERMINATION OF LEADING AQUACULTURE COMMODITIES IN RIAU PROVINCE - Purbata, Ardi Gustri; Nur, M. Irsyad; Simanjuntak, Asnika Putri; Oktavian, Rizki; Firmansyah, Rodhi (Asian Journal of Aquatic Sciences, 2025)
This study aims to identify and analyze leading commodities in the aquaculture sector of Riau Province, using the Location Quotient (LQ), Shift Share, and Klassen Typology approaches. The analysis was conducted on aquaculture production data from 2019 to 2023 to identify commodities with the greatest potential and optimal contribution to the regional economy. The results show that the leading commodities in Riau Province are pangas catfish (Pangasianodon hypophthalmus) and catfish (Clarias gariepinus), both of which have an LQ value greater than 1, indicating that they are basic commodities with high competitiveness at the provincial level. Meanwhile, commodities such as carp (Cyprinus carpio L), Nile tilapia (Oreochromis niloticus), giant goramy (Osphronemus goramy), vaname shrimp (Litopenaeus vannamei), and milkfish (Chanos chanos), despite production fluctuations, still require more efficient management to improve their competitiveness. Based on the shift-share analysis, catfish and tilapia contribute positively and significantly to the growth of the aquaculture sector in Riau Province. Furthermore, the Klassen Typology analysis shows that pangas catfish and catfish fall into the "Advancing and Growing Rapidly" quadrant, while other commodities are in the "Potential or Rapidly Developing" quadrant. This study concludes that the aquaculture sector in Riau Province has great potential for development, particularly for catfish and tilapia, which can be strengthened through improvements in infrastructure, aquaculture technology, and commodity diversification to reduce production fluctuations. Improvement of infrastructure, aquaculture technology, commodity diversification, and farmer training can enhance productivity, quality, and market competitiveness both domestically and internationally in a sustainable manner